2021
DOI: 10.3390/ani11092546
|View full text |Cite
|
Sign up to set email alerts
|

Does Small-Scale Livestock Production Use a High Technological Level to Survive? Evidence from Dairy Production in Northeast-ern Michoacán, Mexico

Abstract: The objective of this study was to identify the technological level used by dairy farmers in the northeastern region of Michoacán, Mexico, through a characterisation of small-scale dairy production units, as well as to learn about the socioeconomic conditions that have enabled them to survive in the current context. A semi-structured interview was applied to 114 production units, chosen by stratified random sampling. The interview included technological, production and socioeconomic aspects. Twenty-eight varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The research conducted by [87] defined three groups of farms in the typology of dairy production systems (DPSs), based on the assessment of economic, social, and environmental factors. As a result of the statistical analysis, the authors of [88] identified four groups of dairy farms differentiated by different levels of technology. The present study covers five categories of farms; size is the key criterion for distinguishing those five categories.…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted by [87] defined three groups of farms in the typology of dairy production systems (DPSs), based on the assessment of economic, social, and environmental factors. As a result of the statistical analysis, the authors of [88] identified four groups of dairy farms differentiated by different levels of technology. The present study covers five categories of farms; size is the key criterion for distinguishing those five categories.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is a strong relationship between the social capital and the income of Kediri beef cattle farmers. It suggested that income increased in direct proportion to social capital (Chávez-Pérez et al, 2021;Lan et al, 2022;Liu et al, 2022a). A social gathering and intense training in technological mastery for farmers were two initiatives to boost social capital (Kamarudin et al, 2021;Khattak et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%